Brand Activism pada Pasar Konsumen dan Dampaknya terhadap Purchase Intention: Peran Brand Trust sebagai Mediating Mechanism - Ivo Arfiani Turnip; Fadli Fadli; Muhammad Dharma Tuah Putra Nasution (Lembaga Yasin AlSys, 2025)
Although brand activism has attracted growing attention in the marketing literature, studies that specifically examine the psychological mechanisms through which brand activism influences purchase intention in emerging markets remain limited. This study aimed to analyze the effect of brand activism on purchase intention with brand trust as a mediating variable in the context of the Indonesian consumer market. A quantitative approach with a cross-sectional survey design was employed, involving 385 millennial and Generation Z respondents in Indonesia selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS 24.0. The results show that brand activism has a significant positive effect on purchase intention (β = 0.412, p < 0.001) and brand trust (β = 0.536, p < 0.001). Brand trust also significantly affects purchase intention (β = 0.539, p < 0.001) and partially mediates the relationship between brand activism and purchase intention (indirect effect = 0.289, p < 0.001), with a total effect of 0.701. These findings contribute to the development of consumer–brand relationship theory by identifying trust as a critical mediating mechanism and by extending understanding of the effectiveness of brand activism in emerging markets with distinctive socio-cultural characteristics. The study concludes that authentic and consistent brand activism is crucial for building consumer trust and encouraging purchase intention, and recommends that brand managers design activism strategies that prioritize authenticity, long-term commitment, and tangible social impact. The implications of this research include a theoretical contribution to the literature on conscious consumerism and practical implications for companies targeting consumers who are concerned with social issues, while also opening opportunities for further research on the differential effects of various types of activism and cultural boundary conditions.